2021
DOI: 10.3390/rel12090737
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Religiosity and Socioeconomic Status on Social Distance towards Refugees and the Serial Mediating Role of Satisfaction with Life and Perceived Threat

Abstract: In every society, refugees face social and economic exclusion. In particular, social distance towards refugees may be seen remarkably in cities where host people and refugees live together intensely. This study examined essential predictors of social distance towards refugees: religiosity, socioeconomic status (SES), satisfaction with life, and threat perception towards refugees. A quantitative research strategy was used to collect cross-sectional data from 1453 individuals via an online questionnaire in Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 109 publications
(159 reference statements)
0
3
0
3
Order By: Relevance
“…3 -Türk vatandaşlarının Suriyeli mültecileri geçici (kalıcı yerleşimcilere kıyasla) yerleşimciler olarak gördüklerinde daha az tehdit algıladıkları nı ve Suriyeli mültecileri kabul etmeye daha istekli oldukları sonuçlarına ulaşmıştır. Koçak (2021) çalışmasında, mültecilere yönelik sosyal mesafenin temel yordayıcıları olan dindarlık, sosyoekonomik durum, yaşamdan memnuniyet ve mültecilere yönelik tehdit algısını incelenmiştir. Yaşamdan memnuniyet mültecilere yönelik tehdit algısını olumsuz etkilemektedir.…”
Section: Li̇teratür Taramasiunclassified
“…3 -Türk vatandaşlarının Suriyeli mültecileri geçici (kalıcı yerleşimcilere kıyasla) yerleşimciler olarak gördüklerinde daha az tehdit algıladıkları nı ve Suriyeli mültecileri kabul etmeye daha istekli oldukları sonuçlarına ulaşmıştır. Koçak (2021) çalışmasında, mültecilere yönelik sosyal mesafenin temel yordayıcıları olan dindarlık, sosyoekonomik durum, yaşamdan memnuniyet ve mültecilere yönelik tehdit algısını incelenmiştir. Yaşamdan memnuniyet mültecilere yönelik tehdit algısını olumsuz etkilemektedir.…”
Section: Li̇teratür Taramasiunclassified
“…We also let participants rate their personal understanding of the distinction between the labels (i.e., variable 'Understanding of Labels') because past research indicated that those who were less exposed to confusion between labels showed larger effects of labels on attitudes (Janky, 2019). 2 Finally, we recorded participants' self-perceived social class because social class predicts relevant outcomes related to immigration (e.g., perception of threat and social distance from refugees; Koçak, 2021). Altogether, we tested four moderators: Participants' (a) reported importance of issues regarding immigration, (b) conservative political orientation, (c) understanding of the differences between distinct immigrant labels, and (d) social class.…”
Section: 5mentioning
confidence: 99%
“…Satisfaction with life reflects the gap between one's expectations for the future and what one currently has. The greater the disparity between one's expectations and the things one has currently, the lower one's satisfaction with life (Koçak, 2021). Many studies in the literature have found that low satisfaction with life causes a variety of mental health problems, particularly depression (Lombardo et al, 2018;Moksnes et al, 2014).…”
Section: Satisfaction With Life and Social Functionalitymentioning
confidence: 99%